2019
DOI: 10.1080/16066359.2019.1644323
|View full text |Cite
|
Sign up to set email alerts
|

“We have to put the fire out first before we start rebuilding the house”: practitioners’ experiences of supporting women with histories of substance use, interpersonal abuse and symptoms of post-traumatic stress disorder

Abstract: Introduction and aims: The high prevalence of women experiencing co-occurring substance use, interpersonal abuse, and symptoms of post-traumatic stress disorder (PTSD) has led to international calls for trauma-specific substance use treatments and wider trauma-informed practice. The aim of this study was to explore how services in England have developed practice responses with limited historical precedence for this work. Design and Methods: A purposive sample of 14 practitioners from substance use, interperson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…We suggest that integrated approaches for parental DVA, MH, and SU may need to go beyond these measures to concurrently recognise and address the bi-directional and complex nature of these issues [10][11][12][13][14][15][16], while also addressing the underlying risk factors that may give rise to, or exacerbate, them. Other researchers have highlighted the importance of adopting such an approach, particularly when working with women experiencing DVA, MH, and SU [134][135][136]. In our review, the only study that demonstrated combined impacts on two outcomes (DVA and MH) conceived the relationship between these issues as bi-directional; providing concurrent support for DVA and MH through a culturally informed, empowerment intervention, empathetic-understanding component, and social support from the person delivering the intervention [93].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that integrated approaches for parental DVA, MH, and SU may need to go beyond these measures to concurrently recognise and address the bi-directional and complex nature of these issues [10][11][12][13][14][15][16], while also addressing the underlying risk factors that may give rise to, or exacerbate, them. Other researchers have highlighted the importance of adopting such an approach, particularly when working with women experiencing DVA, MH, and SU [134][135][136]. In our review, the only study that demonstrated combined impacts on two outcomes (DVA and MH) conceived the relationship between these issues as bi-directional; providing concurrent support for DVA and MH through a culturally informed, empowerment intervention, empathetic-understanding component, and social support from the person delivering the intervention [93].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve a gender-informed approach across mental health services, Agenda (2015) calls for women's needs to be explicitly considered in national me ntal health policy and strategy; every mental health trust to appoint a clinical lead for women's mental health and a strategy to take into account women's needs; mental health services to implement routine enquiry about women's experiences of violence and abuse which are accompanied by pathways into proper support and care; dedicated women-only services for women with multiple needs to be available in every area; and frontline workers to receive training on women's mental health, trauma, abuse, and to implement trauma-informed practice. Bailey et al (2019a) argue that a significant 'culture shift' is required in substance use services in England to embrace an approach that recognises the ubiquity of interpersonal abuse (physical, emotional or sexual violence/abuse in adulthood or childhood) experienced by female users, that is 'non-pathologizing, strengths-based, and centred on 'growth-fostering relationships'. Promising practice shows a commitment to understanding women's multiple disadvantage, including an understanding of intersectional disadvantage, experiences of Violence against Women and Girls (VAWG), and associated trauma (Homeless Link, 2018b).…”
Section: Gender-sensitive Approachesmentioning
confidence: 99%
“…There is evidence to suggest that women are more likely to drink heavily when they are also experiencing psychological and/or emotional distress when compared to men (Erol & Karpyak, 2015), suggesting a need for a more psychologically focused approaches to treatment for women. Coupled with the acknowledgement that a large proportion of women who use substances (40-70%) have experienced some form of interpersonal abuse (including physical, sexual, psychological and emotional abuse) there is a need for alcohol treatment services to be able to provide holistic support to women that takes account of these additional needs (Bailey et al, 2020;Thomas & Bull, 2018).…”
Section: Research On Gender and Alcohol Usementioning
confidence: 99%
“…Practitioners working within UK systems of substance use treatment are most likely to reject a medical model of addiction/treatment and tend to work from a strengths-based model (e.g. Bailey et al, 2020). This contrasts with the predominance of the medical model of substance use treatment that informs services based in Poland and has been described as 'homogenous and abstinence-oriented' (Klingemann, 2016, p. 437).…”
Section: Uk Systems and Challenges Of Accessmentioning
confidence: 99%